Regulation of the immune response to pathogens 1 - O’Garra, Anne (Henry Stewart Talks, 2012)
Cell-cell and cytokine interactions regulating the induction and suppression of cellular immune responses, Th1 and Th2 cells in immune regulation, Immunosuppressive functions of IL-10, Inhibition of antigen presentation by dendritic cells and macrophages and reduction in their production of proinflammatory cytokines, Dendritic cells and IL-12 activation of T-cells leading to subsequent eradication of intracellular pathogens, Roles of IL-17, IL-23 and IFN-gamma in pathogenesis and inflammation